Cholesterol-Induced M4-Like Macrophages Recruit Neutrophils and Induce NETosis - Maretti-Mira, Ana C.; Golden-Mason, Lucy; Salomon, Matthew P.; Kaplan, Mariana J.; Rosen, Hugo R. (Frontiers in Immunology, 2021)
The liver is the central organ for cholesterol synthesis and homeostasis. The effects of dietary cholesterol on hepatic injury, mainly of oxidized low-density lipoproteins (OxLDL), are not fully understood. Here, we show that the degree of cholesterol oxidation had different impacts on the global gene expression of human M2-like macrophages, with highly oxidized LDL causing the most dramatic changes. M2-like macrophages and Kupffer cells undergo M4-like polarization, decreasing the expression of important markers, such as IL10, MRC1, and CD163. These cells also displayed functional changes, with reduced phagocytic capacity, increased neutrophil recruitment, and more effective neutrophil extracellular traps (NETs) induction. Our findings provide a link between LDL oxidation and modification of peripheral and liver macrophage function.